1986
DOI: 10.4141/cjss86-016
|View full text |Cite
|
Sign up to set email alerts
|

Crop Residue Management Practices, and N and P Fertilizer Effects on Crop Response and on Some Physical and Chemical Properties of a Black Chernozem Over 25 Years in a Continuous Wheat Rotation

Abstract: . 1986. Crop residue management practices, and N and P fertilizer effects on crop response and on some physical and chemical properties of a Black Chernozem over 25 years in a continuous wheat rotation. Can. J. Soil In the Black soil zone ofthe Canadian Prairies seedbed preparation is important for handling crop residues from high yields and for incorporating herbicides and fertilizers into soil in the fall or prior to seeding in spring. There are numerous tillage implements available to the producer for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 9 publications
2
17
1
Order By: Relevance
“…At Melfort, fertilizer did not affect c€real straw/grain ratio which was 1.5/l (Nuttall et al 1986). Root/straw ratio for wheat assumed to be 0.59 (Campbell et al 1977a).…”
Section: Methodsmentioning
confidence: 99%
“…At Melfort, fertilizer did not affect c€real straw/grain ratio which was 1.5/l (Nuttall et al 1986). Root/straw ratio for wheat assumed to be 0.59 (Campbell et al 1977a).…”
Section: Methodsmentioning
confidence: 99%
“…Lower soilerosion losses under CW than under WWF or WF may be associated with annual inputs of plant residues and the number of tillage operations used for weed control and seedbed preparation. The amount of above-ground plant residues returned to the soil at harvest was estimated by multiplying grain yield by 1.5 (Nuttall et al 1986)' Based on this equation, the average arnount of straw refurned annually was higher under CW (194i kg ha-l) than under W.WF (1603 kg hi-r) or \ fF (1367 kg hrl). An exponential function with negative slope described the effect of straw addition on rate of soil erosion (Fig.…”
mentioning
confidence: 99%
“…However, in our study, RT and SRet did not show any significant effect on residual nitrate-N in soil at both sites compared to the corresponding NT and SRem treatments after 32 years. Similarly, earlier studies in Saskatchewan (Nuttall et al, 1986) and Alberta (Malhi et al, 2006Malhi & Lemke, 2007) have also shown no effect of tillage or straw management on residual soil nitrate-N. This lack of difference in residual nitrate-N in soil due to RT or SRet in this study could be due to uptake of all mineralized nitrate-N by crops in the growing seasons, resulting in little or no additional residual nitrate-N in soil after harvest compared to NT, as evidenced by greater crop yield and N uptake with RT and SRet than corresponding NT and SRem treatments (Malhi et al, 2011b(Malhi et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%